Dust-extinction-curve Variation in the Translucent Interstellar Medium Is Driven by Polycyclic Aromatic Hydrocarbon Growth - Xiangyu Zhang; Brandon S. Hensley; Gregory M. Green (The Astrophysical Journal Letters)
The first all-sky, high-resolution, 3D map of the optical extinction curve of the Milky Way revealed an unexpected steepening of the extinction curve in the moderate-density, “translucent” interstellar medium (ISM). We argue that this trend is driven by growth of the total mass of polycyclic aromatic hydrocarbons (PAHs) through gas-phase accretion. We find a strong anticorrelation between the slope of the optical extinction curve—parameterized by R ( V )—and maps of the PAH mass fraction (relative to the total dust mass)—parameterized by q _PAH —derived from infrared emission. The range of observed q _PAH indicates PAH growth by a factor of ∼2 between A _V  ≃ 1 and 3. This implies a factor-of-2 stronger 2175 Å feature, which is sufficient to lower R ( V ) by the observed amount. This level of PAH growth is possible given rapid accretion timescales and the depletion of carbon in the translucent ISM. Spectral observations by JWST would provide a definitive test of this proposed explanation of R ( V ) variation.